Conducting Counseling About Diabetes Mellitus in Desa Perkebunan Tanjung Kasau. Kec, Laut Tador. Kab, Batu Bara - Manalu, Sarah Patumona; Nurzanna, Tasya Nabilla (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Diabetes mellitus is a chronic disease characterized by high glucose levels. Diabetes mellitus if not handled properly can cause various complications in organs such as the eyes, kidneys, heart, blood vessels and nerves which will endanger the life and affect a person's quality of life. Complications can be acute and chronic. The purpose of this article is to provide an overview of knowledge about diabetes mellitus through counseling. The method used is direct mass counseling using power point slides. The results obtained were that the extension activities went well, the participants listened and asked questions actively from start to finish.